Alterations of Chromatin Regulators in the Pathogenesis of Urinary Bladder Urothelial Carcinoma - Hoffmann, Michèle J.; Schulz, Wolfgang A. (Cancers, 2021)
Urothelial carcinoma (UC) is the most frequent histological type of cancer in the urinary bladder. Genomic changes in UC activate MAPK and PI3K/AKT signal transduction pathways, which increase cell proliferation and survival, interfere with cell cycle and checkpoint control, and prevent senescence. A more recently discovered additional category of genetic changes in UC affects chromatin regulators, including histone-modifying enzymes (KMT2C, KMT2D, KDM6A, EZH2), transcription cofactors (CREBBP, EP300), and components of the chromatin remodeling complex SWI/SNF (ARID1A, SMARCA4). It is not yet well understood how these changes contribute to the development and progression of UC. Therefore, we review here the emerging knowledge on genomic and gene expression alterations of chromatin regulators and their consequences for cell differentiation, cellular plasticity, and clonal expansion during UC pathogenesis. Our analysis identifies additional relevant chromatin regulators and suggests a model for urothelial carcinogenesis as a basis for further mechanistic studies and targeted therapy development.